Trichoderma reesei Cellulase Complex in Hydrolysis of Agricultural Waste of Grapefruit Peel and Orange Peel - I-Son Ng; Xiaomin Wu; Yinghua Lu; Chuanyi Yao (BioResources, 2014)
Previous attempts have already been performed for the production of sugars and, later, bioproducts from orange peel using different Trichoderma reesei commercial cocktails in combination with other kinds of enzymes. In this study, the feasibility of simple pretreatments combined with enzymatic treatments was compared between grapefruit inner peel (GFIP), orange inner peel (OIP), grapefruit whole peel (GFWP), and orange whole peel (OWP). The four biomaterials were characterized with respect to the contents of cellulose and hemi-cellulose, elemental analysis, and Fourier transform infrared (FTIR) spectrometry. The 3,5-dinitrosalicylic acid assay demonstrated that GFIP and OIP produced 31.7% and 34.9% more reducing sugar than GFWP and OWP, respectively. Further investigation of the bioprocess showed the optimal conditions include the following: (i) a solid to liquid ratio of 4%, (ii) enzymatic activity of 0.075 U/mL, and (iii) reaction at 55 °C and a pH of 5.0. Moreover, the major products after cellulolytic hydrolysis were fructose, glucose, and cellobiose. This study provides an alternative and effective approach to extend the utilization of agricultural waste in the fields of food and energy.